Study Of The Effectiveness Of The Use Of Gypsum And Volcanic Ash On Stability Of The Clay Soil Based On The CBR Value And The Unconfined Compression Test - Ade Indra Utama Lubis (IHSA Institute, 2021)
Stabilization is one of the efforts to improve the condition of the soil which has a poor index of properties. One of the soil stabilization that is usually done is by adding chemicals to the soil. Chemicals commonly used in the form of cement, lime, bitumen. In this study, the stabilization of clay was carried out by adding gypsum and volcanic ash. The purpose of this study was to determine the value of the index properties due to the addition of 2% gypsum and volcanic ash on the clay soil, then to determine the maximum compressive strength value due to the addition of variations in stabilizing materials by testing the Unconfined Compression Test (UCT) and testing the California Bearing Ratio (CBR). ) laboratory. From the research, it was found that the original soil sample had a moisture content of 12.42%; specific weight 2.65; liquid limit 46.82% and plasticity index 29.40%. The original soil classification according to USCS is classified as Clay – Low Plasticity (CL) and according to AASHTO it is classified as A-7-6 (10). Unconfined Compression Test (UCT) values ​​for native soil and native soil plus 2% gypsum were 1.40 kg/cm2 and 1.66 kg/cm2. The laboratory CBR values ​​for soaked and unsoaked for the original soil were 4.44% and 6.28%, respectively. While the laboratory CBR values ​​soaked and unsoaked for the original soil plus 2% gypsum were 6.74% and 8.02%, respectively.The most effective results were obtained from a mixture of 2% gypsum and 10% volcanic ash with a UCT value of 2.79 kg/cm2 (an increase of 99.28%). For laboratory CBR testing, the most effective mixture was on a mixed variation of 2% gypsum and 9% volcanic ash with laboratory CBR values ​​soaked and unsoaked of 9.07% (an increase of 104.27% from the original soil) and 10 ,29% (an increase of 63.85% from the original land). The soil that has been mixed with the most effective stabilizer material, namely 2% gypsum and 9% volcanic ash is classified as Clay - Low Plasticity (CL) based on the USCS classification and is classified as A-6 (4) based on the AASHTO classification.